Kepelbagaian isu dalam pentadbiran dan pembangunan di Malaysia - Che Su Mustaffa; Wan Ab. Rahman Khudzri Wan Abdullah; Rohani Ab. Ghani; Penerbit Universiti Utara Malaysia (Sintok : Penerbit Universiti Utara Malaysia, 2006)
Social, economic, and political issues in terms of management and development in Malaysia; papers of a colloquium.
Keywords: Malaysia -- Social conditions -- Congresses; Malaysia -- Economic conditions -- Congresses; Malaysia -- Politics and government -- Congresses